EXPLORING THE DIPLOMATIC, POLITICAL AND ECONOMIC RELATIONS BETWEEN NIGERIA AND THE UNITED KINGDOM - Agubo, Onajiyoma C.; Folarin, Sheriff F (International Journal of Psychosocial Rehabilitation, 2020)
Nigeria became a sovereign independent State by 1960 and since then Nigeria has continued to nurture diplomatic relations with Western capitalist nations such as Britain, France, Germany and the United States. This article scrutinises the changing pattern and nature of relations between Nigeria and the United Kingdom since gaining independence in 1960. It states that relations between the countries have greatly improved due to a number of domestic, diplomatic, political and economic changes that occurred in both countries, as well as the changes of the global world. The paper elucidates the explicit factors that have influenced the Nigerian-UK relations in more recent times and the unending bond that could lead to the eradication of underdevelopment in all its facets. It also exposes the positive and negative views of such relations using mostly published sources from a historical perspective. This research made use of secondary data. The findings are that economic and political diplomacy has contributed to the development of Nigeria as a State however it concludes that Nigeria needs to learn from countries in the East like China, India and Japan using the lessons of the Asian Tigers for its development.